New Investment Rulemaking in Asia: Between Regionalism and Domestication. Issue 1 (February 2023) - Hsieh, Pasha L.
Abstract: The article analyses investment rulemaking in new Asian regionalism in the context of evolving national legislation and regional trade strategies. It argues that the Association of Southeast Asian Nations (ASEAN) and the Regional Comprehensive Economic Partnership (RCEP) represent Asia's pragmatic incrementalism in reforming the investment regime. The process reinforces the relationship between international economic law and domestic investment laws. In tandem with transforming international investment agreements, ASEAN expedited investment and services trade, and established the modern investor–state dispute settlement (ISDS) mechanism. The RCEP further buttresses the ASEAN centrality in regional frameworks by consolidating ASEAN Plus One agreements. Yet, the RCEP's omission of ISDS reflects a distinct approach that may confront challenges to state-to-state proceedings and treaty shopping under overlapping pacts. Finally, the research sheds light on Asian countries' recent investment agreements and domestic dispute settlement that complement the liberal international order. These developments provide valuable models for developing countries and contribute to the understanding of global investment reforms from an Asian perspective.